FDM mixture suitable for preparing aluminum silicon carbide composite material through FDM printing, preparation method and application of FDM mixture

By designing an aluminum silicon carbide composite FDM mixture suitable for FDM printing, combined with FDM printing, thermal degreasing and pressure-free impregnation, the problems of complex preparation process and insufficient material performance in traditional technology have been successfully solved, and low-cost, high-efficiency manufacturing and excellent performance of aluminum silicon carbide composites of complex structures have been achieved.

CN119681260APending Publication Date: 2025-03-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410264608.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

It is difficult to prepare aluminum silicon carbide composite materials through FDM printing technology in the prior art, and traditional molding technology has problems such as complex mold design and manufacturing, high cost, and prone to crack defects during material processing.

Method used

A FDM mixture of aluminum silicon carbide composite material suitable for FDM printing, including silicon carbide powder, aluminum powder, organic binder and surfactant, was designed. The mixture was prepared by ball milling and intensive refining, and the aluminum silicon carbide composite material was successfully prepared by FDM printing, thermal degreasing and pressure-free impregnation.

Benefits of technology

The application of FDM printing technology in the preparation of aluminum silicon carbide composite materials has been realized, the production process is simplified, the development cycle is shortened, the processing efficiency is improved, and excellent mechanical and thermal properties are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119681260A_ABST
    Figure CN119681260A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of additive manufacturing and metal-based composite materials, in particular to an FDM mixture suitable for preparing an aluminum silicon carbide composite material through FDM printing, a preparation method and application of the FDM mixture. The FDM mixture comprises the following raw materials: silicon carbide powder, aluminum powder, an organic binder and a surfactant; carrying out FDM printing on the FDM mixed material to form an aluminum silicon carbide composite material preform, carrying out thermal degreasing on the preform to obtain a biscuit, and carrying out aluminum infiltration on the biscuit by using a pressureless infiltration method to obtain the aluminum silicon carbide composite material. The environment-friendly and cheap method for preparing the aluminum silicon carbide composite material based on FDM printing is successfully developed, the aluminum silicon carbide composite material with excellent mechanical properties and thermal properties can be prepared, and low-cost and near-net-size efficient manufacturing of the aluminum silicon carbide composite material with a complex structure can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of additive manufacturing and the technical field of metal-based composite materials, and in particular to an FDM mixture suitable for FDM printing to prepare aluminum silicon carbide composite materials, a preparation method and applications thereof. Background Art

[0002] Aluminum-silicon carbide composites have enormous application potential in the fields of structural materials and electronic packaging materials due to their high specific strength, specific modulus, and good thermal conductivity. At the same time, traditional molding techniques for aluminum-silicon carbide composites, such as stir casting and compression molding, require the use of molds during the preparation process. The design and manufacture of molds makes the entire production cycle time-consuming and costly, and there are significant limitations in the manufacture of aluminum-silicon carbide composite components with complex shapes and composite structures, making it difficult to achieve highly complex geometries. Aluminum-silicon carbide composites are also prone to SiC particle dissociation, fragmentation, and shedding during processing, resulting in crack defects.

[0003] Additive manufacturing (AM) technology eliminates the need for molds and utilizes the principle of layer-by-layer fabrication. Theoretically, it can form any complex structure as a whole, making it an effective approach for achieving the integration, lightweighting, and complex molding of complex components. AM, which deposits materials point by point, line by line, or surface by surface to create a defined component shape, is not restricted by mold production or machining processes, offering unique advantages in the molding of complex components.

[0004] Currently, mainstream additive manufacturing technologies include selective laser sintering, selective laser melting, stereolithography, direct ink writing, and fused deposition modeling (FDM) printing. In recent years, FDM printing has broken through the limitations of traditional filament materials, replacing traditional plastic filaments with mixed particles, providing a new solution for large-scale, high-efficiency, and low-cost printing.

[0005] Currently, there are no reports on the use of FDM printing technology to prepare aluminum silicon carbide composites. Using FDM printing technology to prepare aluminum silicon carbide composites is expected to achieve the preparation of complex structures, the control of silicon carbide volume fraction and performance. Summary of the Invention

[0006] The present invention addresses the deficiencies in the prior art and aims to provide an FDM mixture suitable for preparing aluminum-silicon carbide composite materials using FDM printing, a preparation method thereof, and a method for preparing aluminum-silicon carbide composite materials using FDM printing. The invention achieves the successful preparation of aluminum-silicon carbide composite materials using FDM printing technology.

[0007] One object of the present invention is achieved by the following technical solutions:

[0008] An FDM mixture suitable for FDM printing to prepare aluminum silicon carbide composite materials, wherein the raw materials of the FDM mixture include silicon carbide powder, aluminum powder, an organic binder, and a surfactant;

[0009] The volume of the silicon carbide powder accounts for 1 to 99% of the total volume of the silicon carbide powder and the aluminum powder, the mass of the surfactant is 0.5 to 25 wt% of the mass of the organic binder, and the mass of the organic binder is 1 to 35 wt% of the total mass of the FDM mixture;

[0010] The FDM mixture is prepared into an aluminum silicon carbide composite material through an FDM printing step.

[0011] Preferably, the particle size distribution of the silicon carbide powder is D50 = 0.5 to 150 μm, more preferably D50 = 1 to 70 μm.

[0012] Preferably, the surfactant is selected from one or more of silane coupling agents, stearic acid, stearate, polyethyleneimine and tetramethylammonium hydroxide.

[0013] The silane coupling agent may be exemplified by one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, γ-aminoethylaminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and 3-glycidoxypropylmethyldiethoxysilane.

[0014] Examples of stearates include one or more of sodium stearate, calcium stearate, magnesium stearate, zinc stearate, aluminum stearate, and barium stearate.

[0015] Preferably, the organic binder is one or more of a wax-based binder, epoxy resin, polyethylene glycol, high-density polyethylene, paraffin, polylactic acid, and ethylene-vinyl acetate copolymer.

[0016] Wax-based adhesive is a composite adhesive with paraffin as the main raw material.

[0017] More preferably, the organic binder is a mixture of paraffin wax, ethylene-vinyl acetate copolymer and high-density polyethylene. More preferably, the organic binder is a mixture of paraffin wax, ethylene-vinyl acetate copolymer and high-density polyethylene in a mass ratio of 1-5:1-5:1-5.

[0018] Preferably, the volume of the silicon carbide powder accounts for 1-90% of the total volume of the silicon carbide powder and the aluminum powder, the mass of the surfactant is 1-10wt% of the mass of the organic binder, and the mass of the organic binder is 1-30wt% of the total mass of the FDM mixture.

[0019] Preferably, the FDM mixture is prepared into an aluminum silicon carbide composite material through the steps of FDM printing, thermal degreasing, and infiltration of aluminum by a pressureless infiltration method.

[0020] The second object of the present invention is achieved through the following technical solutions:

[0021] The aforementioned method for preparing an FDM mixture suitable for FDM printing to prepare aluminum silicon carbide composite materials comprises the following steps: mixing silicon carbide powder, aluminum powder and a surfactant to obtain a modified powder; kneading the modified powder with an organic binder, and then granulating to obtain an FDM mixture.

[0022] The silicon carbide powder, aluminum powder, and surfactant can be mixed using a ball milling method. Specifically, the silicon carbide powder, aluminum powder, and surfactant are added to a ball mill, anhydrous ethanol is added, and the mixture is milled. For example, silicon carbide balls are used as the milling medium, the milling speed is 100 to 600 rpm, the ball-to-material ratio is 1 to 50:1, and the milling time is 0.5 to 10 hours. The milled slurry is then dried to obtain the modified powder.

[0023] The internal mixing is carried out in an internal mixer at a mixing temperature of 130 to 180° C. and a mixing time of 1 to 5 hours. The granulation is carried out in a granulator at an extrusion pressure of 1 to 10 MPa.

[0024] The third object of the present invention is achieved through the following technical solutions:

[0025] A method for preparing aluminum silicon carbide composite materials based on FDM printing, comprising the following steps:

[0026] The aforementioned FDM mixture is used for FDM printing to form an aluminum silicon carbide composite material preform; the preform is thermally degreased to obtain a green blank; and the green blank is infiltrated with aluminum using a pressureless infiltration method to obtain the aluminum silicon carbide composite material.

[0027] Before FDM printing, first use drawing software to draw a three-dimensional model of the spatial structure of the required prefabricated part, and then perform layering to determine the parameters of three-dimensional molding and form an operation trajectory code. This step is a commonly used operation method in the field and is simple and convenient to operate. In the industrial application of composite materials, the spatial shape of the printed prefabricated body can be flexibly changed according to the specific working conditions. In this technical solution, the printed prefabricated body can be designed into different shapes according to needs, the operation is flexible and diverse, and various complex shapes can be formed.

[0028] FDM printing is performed using an FDM type 3D printer. Preferably, the nozzle temperature is 150-200° C., the printing platform temperature is 90-120° C., and the nozzle aperture is 0.4-1 mm.

[0029] Preferably, the thermal debinding process includes heating the material to 500-1000°C at an average heating rate of 0.1-5°C / min, performing the thermal debinding for 0.5-20 hours, and performing the thermal debinding in a vacuum environment. More preferably, the thermal debinding temperature is 600-900°C, and the thermal debinding time is 0.5-5 hours.

[0030] Preferably, the pressureless infiltration process includes: adopting an inert atmosphere, an infiltration temperature of 700-1000° C., and an infiltration time of 0.5-5 h.

[0031] Examples of the inert atmosphere include nitrogen and argon.

[0032] Specifically, a method for preparing an aluminum silicon carbide composite material based on FDM printing comprises the following steps:

[0033] Silicon carbide powder, aluminum powder and a surfactant are mixed to obtain a modified powder; the modified powder is kneaded with an organic binder and then granulated to obtain an FDM mixture;

[0034] The FDM mixture is subjected to FDM printing to form an aluminum silicon carbide composite material preform; the preform is thermally degreased to obtain a green blank; and the green blank is infiltrated with aluminum using a pressureless infiltration method to obtain the aluminum silicon carbide composite material.

[0035] The fourth object of the present invention is achieved through the following technical solutions:

[0036] The aluminum silicon carbide composite material prepared according to the above method has a density of 2.60-3.00 g / cm 3 , three-point bending strength is 150~300MPa, thermal conductivity is 80~200W / m*K, thermal expansion coefficient is 5~15*10 -6 / K; the volume fraction of SiC in the aluminum silicon carbide composite material is in the range of 1 to 80%.

[0037] The principles and advantages of this patent are:

[0038] When using traditional molds to prepare preforms, it is found that the process is complicated and tedious, and it is difficult to demold after molding. In addition, when preparing materials with complex spatial structures, traditional processing methods are prone to damage to the samples. However, the inventors have designed an FDM mixture suitable for FDM printing to prepare aluminum silicon carbide composite materials and a method for preparing aluminum silicon carbide composite materials based on FDM printing. This can avoid the use of molds and the tedious process of demolding in the traditional aluminum silicon carbide preparation process, while avoiding damage to the difficult-to-process aluminum silicon carbide composite materials during the processing process. It can directly prepare aluminum silicon carbide composite materials with three-dimensional structures of any shape and adjustable silicon carbide volume fraction, simplifying the preparation process, shortening the development cycle, and improving processing efficiency.

[0039] During their research, the inventors discovered that when the FDM mixture does not include aluminum powder, the blanks produced after FDM printing and thermal degreasing are difficult to infiltrate with aluminum under pressureless conditions. Therefore, the pressureless infiltration process cannot be used to infiltrate aluminum, and a high-pressure infiltration process must be used. However, high-pressure infiltration requires the design of a mold that matches the shape of the blank, which is too expensive, and high pressure will also destroy the complex shape of the blank. Therefore, when the FDM mixture does not include aluminum powder, it is impossible to produce high-quality, complex-shaped aluminum-silicon carbide composites through FDM printing. The inventors have researched and designed an FDM mixture composed of silicon carbide, aluminum, an organic binder, and a surfactant. After 3D printing and thermal degreasing, the blanks produced can be infiltrated with aluminum under pressureless conditions, making it possible to produce aluminum-silicon carbide composites through FDM printing.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The present invention successfully realizes the preparation of aluminum silicon carbide composite materials by FDM printing through the design of FDM mixtures and the steps of preparing aluminum silicon carbide composite materials by FDM printing based on the FDM mixtures, and realizes the low-cost and near-net-size efficient manufacturing of aluminum silicon carbide composite materials with complex structures. The prepared aluminum silicon carbide composite materials have excellent mechanical properties and thermal properties.

[0042] (2) The present invention prepares aluminum silicon carbide composite materials through FDM printing, which can avoid the tedious process of using molds and demolding in the traditional aluminum silicon carbide preparation process, and at the same time avoid damage to the difficult-to-process aluminum silicon carbide composite materials during the processing process. It can directly prepare aluminum silicon carbide composite materials with three-dimensional structures of any shape and adjustable silicon carbide volume fraction, simplify the preparation process, shorten the development cycle, and improve processing efficiency.

[0043] (3) By adjusting the volume fraction of silicon carbide powder in the FDM mixture, the volume fraction of silicon carbide in the dense aluminum silicon carbide composite material after pressureless infiltration of aluminum can be adjusted. The silicon carbide volume fraction of the obtained aluminum silicon carbide composite material can be regulated within a certain range, and further the properties including mechanical properties and thermal properties can be regulated. In application fields such as electronic packaging, complex molding of parts and performance control of parts can be achieved.

[0044] (4) The aluminum silicon carbide composite material printed by combining FDM type 3D printing and pressureless infiltration has a high solid content and a good morphology after degreasing, and can maintain the printed shape intact; the aluminum and silicon carbide are evenly distributed inside the aluminum silicon carbide composite material after pressureless infiltration, and the material size can maintain a complex shape, which can achieve near-net forming of complex shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 These are actual pictures of the aluminum silicon carbide composite material preform prepared in step (2) of Example 1 of the present invention (first from the left), the aluminum silicon carbide composite material blank obtained by thermal degreasing in step (3) (second from the left), and the aluminum silicon carbide composite material of complex shape obtained in step (4) (first and second from the right).

[0046] Figure 2 This is a microscopic morphology of the aluminum silicon carbide composite material prepared based on FDM 3D printing in Example 1 of the present invention.

[0047] Figure 3 This is the XRD phase analysis diagram of the aluminum silicon carbide composite material based on FDM 3D printing prepared in Example 1 of the present invention.

[0048] Figure 4 This is a physical picture of the aluminum silicon carbide composite material prepared based on FDM 3D printing in Example 2 of the present invention.

[0049] Figure 5 This is a comparison diagram of the surface morphologies of the printed preform, degreased blank, and dense material after pressureless infiltration of the aluminum silicon carbide composite material based on FDM-type 3D printing prepared in Example 3 of the present invention. From top to bottom, they are the surface morphologies of the printed preform, degreased blank, and dense material after pressureless infiltration. DETAILED DESCRIPTION

[0050] Below by specific embodiment and accompanying drawing, technical scheme of the present invention is further described explanation, it should be understood that specific embodiment described herein is only for helping to understand the present invention, is not used for specific limitation of the present invention.And accompanying drawing used herein, is only for better illustrating the disclosure of the present invention, does not have limiting effect on protection scope.If no special instructions, the raw materials adopted in the embodiment of the present invention are all raw materials commonly used in this area, and the method adopted in the embodiment is all conventional method in this area.

[0051] In the following examples and comparative examples:

[0052] The organic binder is a mixture of paraffin wax, ethylene-vinyl acetate copolymer and high-density polyethylene in a mass ratio of 2:1:1. High-density polyethylene was purchased from Taihe Plastic Raw Materials Business Department in Zhangmutou, Dongguan City; paraffin wax was purchased from Kaixuan Plastic Technology Co., Ltd.; and ethylene-vinyl acetate copolymer was purchased from Hongxin Plastic Raw Materials Business Department in Zhangmutou, Dongguan City.

[0053] The D50 of silicon carbide powder is 50 μm.

[0054] Example 1

[0055] The raw materials for preparing the FDM mixture of this embodiment are silicon carbide powder, aluminum powder, an organic binder, and a surfactant, stearic acid. Among them, the volume of silicon carbide powder accounts for 60% of the total volume of silicon carbide powder and aluminum powder, the mass of stearic acid is 5wt% of the mass of the organic binder, and the mass of the organic binder is 15wt% of the total mass of the FDM mixture.

[0056] The method for preparing an aluminum silicon carbide composite material based on FDM printing in this embodiment includes the following steps:

[0057] (1) Preparation of FDM mixture: According to the above-mentioned FDM mixture formula, each raw material was weighed, and silicon carbide powder, aluminum powder, and stearic acid were added to a ball mill. Anhydrous ethanol was added and ball milled for 4 hours using silicon carbide balls as the ball milling medium. The ball milling speed was 300 rpm and the ball-to-material ratio was 1:1. The ball-milled slurry was placed in an oven to dry to obtain a modified powder. The modified powder was mixed with an organic binder in an internal mixer at a mixing temperature of 140°C and a mixing time of 2 hours. Then, granulation was carried out in a direct pressure granulator with an extrusion pressure of 3 MPa to obtain particles suitable for FDM mixture.

[0058] (2) FDM printing: First, a three-dimensional model of the spatial structure of the preform is drawn using drawing software, and then layered, the parameters of three-dimensional molding are determined, and a running trajectory code is formed; the FDM mixture particles prepared in step (1) are used as raw materials, and an FDM type 3D printer is used to print and shape the aluminum silicon carbide composite preform. The printing nozzle temperature is set to 170°C, the printing platform temperature is set to 100°C, and the nozzle aperture is 0.8mm.

[0059] (3) Thermal degreasing: The aluminum silicon carbide composite material preform prepared in step (2) is placed in an oven for curing and thermal degreasing is performed using a vacuum furnace. The thermal degreasing atmosphere is a vacuum environment and the temperature is increased to 600°C at an average heating rate of 1°C / min. The thermal degreasing time is 20 hours, and an aluminum silicon carbide composite material blank can be obtained.

[0060] (4) Pressureless Infiltration: The aluminum-silicon carbide composite material blank obtained in step (3) is placed in a crucible, aluminum powder is laid on the preform, and the preform is placed in a vacuum sintering furnace for pressureless aluminum infiltration. In a nitrogen atmosphere, the aluminum is infiltrated at 950°C for 1 hour to obtain the aluminum-silicon carbide composite material based on FDM 3D printing.

[0061] After testing, the density of the aluminum-silicon carbide composite material obtained after pressureless aluminum infiltration in this embodiment is 2.70g / cm 3 , three-point bending strength is 202MPa, thermal conductivity is 124 (W / m*K), thermal expansion coefficient is 10.52*10 -6 / K, SiC volume fraction is 38%.

[0062] Figure 1 The following are images of the aluminum-silicon carbide composite preform prepared in step (2) of Example 1 of the present invention (first left), the aluminum-silicon carbide composite blank obtained by thermal degreasing in step (3) (second left), and the aluminum-silicon carbide composite material of complex shape obtained in step (4) (first and second right). As can be seen from the figure, the blanks formed by 3D printing are highly accurate, with clear edge contours and no drooping. The thermally degreased blanks show almost no dimensional shrinkage compared to the printed preforms, and the printed shape is well maintained.

[0063] Figure 2 This is a microscopic image of the aluminum-silicon carbide composite material prepared using FDM 3D printing in Example 1. As can be seen from the image, after pressureless aluminum infiltration, the aluminum-silicon carbide composite material has a uniform and dense microstructure, with no segregation of silicon carbide or aluminum.

[0064] Figure 3This is an XRD phase analysis diagram of the aluminum-silicon carbide composite material prepared using FDM 3D printing, as described in Example 1 of the present invention. As can be seen from the figure, the sample after pressureless aluminum infiltration is primarily composed of SiC, Al, Al4C3, and Si. Due to the high temperature and nitrogen atmosphere of the pressureless infiltration, a small amount of Al4C3 and pure Si phase is present.

[0065] Example 2

[0066] The only difference between Example 2 and Example 1 is that the volume of silicon carbide powder in Example 2 accounts for 70% of the total volume of silicon carbide powder and aluminum powder, and the printer nozzle temperature is set to 175° C. The rest is the same as Example 1.

[0067] The density of the aluminum-silicon carbide composite material obtained after pressureless aluminum infiltration in Example 2 is 2.73 g / cm 3 , three-point bending strength is 211MPa, thermal conductivity is 112 (W / m*K), thermal expansion coefficient is 8.67*10 -6 / K, SiC volume fraction is 43%.

[0068] Figure 4 This is a photo of the aluminum-silicon carbide composite material produced using FDM 3D printing, as described in Example 2 of the present invention. The image shows minimal dimensional shrinkage compared to the printed preform and the degreased blank, achieving near-net-shape production of the complex aluminum-silicon carbide composite material.

[0069] Example 3

[0070] The only difference between Example 3 and Example 1 is that the volume of silicon carbide powder in Example 3 accounts for 50% of the total volume of silicon carbide powder and aluminum powder, and the printer nozzle temperature is set to 175° C. The rest is the same as Example 1.

[0071] The density of the aluminum-silicon carbide composite material obtained after pressureless aluminum infiltration in Example 3 is 2.73 g / cm 3 , three-point bending resistance is 253MPa, thermal conductivity is 104 (W / m*K), thermal expansion coefficient is 10.241*10 -6 / K, SiC volume fraction is 33%.

[0072] Figure 5 Comparative images of the surface morphology of the aluminum-silicon carbide composite preform (top), degreased green blank (center), and dense material after pressureless infiltration (bottom) produced using FDM 3D printing, as described in Example 3 of the present invention. As can be seen, the printed green blank exhibits excellent morphology and precision, maintaining its shape and surface morphology throughout the entire production process.

[0073] Example 4

[0074] The only difference between Example 4 and Example 1 is that the volume of silicon carbide powder in Example 4 accounts for 30% of the total volume of silicon carbide powder and aluminum powder, and the printer nozzle temperature is set to 175° C. Other steps are the same as in Example 1.

[0075] The density of the aluminum-silicon carbide composite material obtained after pressureless aluminum infiltration in Example 4 is 2.614 g / cm 3 , three-point bending resistance is 195MPa, thermal conductivity is 87 (W / m*K), thermal expansion coefficient is 13.46*10 -6 / K, SiC volume fraction is 19%.

[0076] Example 5

[0077] The raw materials for preparing the FDM mixture of this embodiment are silicon carbide powder, aluminum powder, an organic binder, and a surfactant, KH-550. The volume of the silicon carbide powder accounts for 80% of the total volume of the silicon carbide powder and the aluminum powder, the mass of KH-550 accounts for 8wt% of the mass of the organic binder, and the mass of the organic binder accounts for 20wt% of the total mass of the FDM mixture.

[0078] The method for preparing an aluminum silicon carbide composite material based on FDM printing in this embodiment includes the following steps:

[0079] (1) Preparation of FDM mixture: According to the above-mentioned FDM mixture formula, each raw material was weighed, and silicon carbide powder, aluminum powder, and KH-550 were added to a ball mill. Anhydrous ethanol was added and ball milled for 4 hours using silicon carbide balls as the ball milling medium. The ball milling speed was 250 rpm and the ball-to-material ratio was 1:1. The ball-milled slurry was placed in an oven to dry to obtain a modified powder. The modified powder was mixed with an organic binder in an internal mixer at a mixing temperature of 150°C and a mixing time of 2 hours. Then, granulation was performed using a direct pressure granulator with an extrusion pressure of 5 MPa to obtain particles suitable for FDM mixture.

[0080] (2) FDM printing: First, a three-dimensional model of the spatial structure of the preform is drawn using drawing software, and then layered, the parameters of three-dimensional molding are determined, and a running trajectory code is formed; the FDM mixture particles prepared in step (1) are used as raw materials, and an FDM type 3D printer is used to print and shape the aluminum silicon carbide composite preform. The printing nozzle temperature is set to 180°C, the printing platform temperature is set to 110°C, and the nozzle aperture is 0.8mm.

[0081] (3) Thermal degreasing: The aluminum silicon carbide composite material preform prepared in step (2) is placed in an oven for curing and thermal degreasing is performed using a vacuum furnace. The atmosphere for thermal degreasing is a vacuum environment. The temperature is raised to 650°C at an average heating rate of 0.8°C / min. The thermal degreasing time is 18 hours, and an aluminum silicon carbide composite material blank can be obtained.

[0082] (4) Pressureless Infiltration: The aluminum-silicon carbide composite material blank obtained in step (3) is placed in a crucible, aluminum powder is laid on the preform, and the preform is placed in a vacuum sintering furnace for pressureless aluminum infiltration. In a nitrogen atmosphere, the aluminum is infiltrated at 900°C for 1 hour to obtain the aluminum-silicon carbide composite material based on FDM 3D printing.

[0083] After testing, the density of the aluminum-silicon carbide composite material obtained after pressureless aluminum infiltration in this embodiment is 2.703 g / cm 3 , three-point bending resistance is 208MPa, thermal conductivity is 110 (W / m*K), thermal expansion coefficient is 5.3*10 -6 / K, SiC volume fraction is 53%.

[0084] Comparative Example 1

[0085] Comparative Example 1 differed from Example 1 only in that the volume of silicon carbide powder in Comparative Example 1 accounted for 50% of the total volume of silicon carbide powder and aluminum powder, the mass of the organic binder was 40 wt % of the total mass of the FDM mixture, and the printer nozzle temperature was set to 165°C. All other conditions were the same as in Example 1.

[0086] In Comparative Example 1, since the organic binder accounts for a relatively high proportion by mass in the aluminum silicon carbide composite material printed preform, the aluminum silicon carbide composite material blank obtained after thermal degreasing in this comparative example has a loose structure, lacks bonding force between the inorganic powders, and has no strength to undergo further pressureless infiltration.

[0087] Comparative Example 2

[0088] The FDM mixture of Comparative Example 2 is silicon carbide powder, an organic binder, and stearic acid; wherein the mass of the stearic acid is 5 wt % of the mass of the organic binder, and the mass of the organic binder is 15 wt % of the total mass of the FDM mixture.

[0089] In Comparative Example 2, a degreased silicon carbide blank was obtained by printing and debonding. When pressureless aluminum infiltration was performed using the same process as in Example 1, aluminum infiltration could not be achieved in the final material.

[0090] The various aspects, embodiments, and features of the present invention should be considered in all respects as illustrative and not limiting, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0091] In the preparation method of the present invention, the order of the steps is not limited to the order listed. Persons skilled in the art will appreciate that variations in the order of the steps are within the scope of the present invention without inventive effort. Furthermore, two or more steps or actions may be performed simultaneously.

[0092] Finally, it should be noted that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit its implementation. Persons skilled in the art may make various modifications, additions, or substitute similar methods for the described specific embodiments. It is not necessary and impossible to provide comprehensive examples of all implementations here. However, obvious variations or modifications arising from the essential spirit of the present invention remain within the scope of protection of the present invention, and interpreting them as any additional limitations would be contrary to the spirit of the present invention.

Claims

1. An FDM mixture suitable for FDM printing to prepare aluminum silicon carbide composite materials, characterized in that: The raw materials of the FDM mixture include silicon carbide powder, aluminum powder, organic binder and surfactant; The volume of the silicon carbide powder accounts for 1-99% of the total volume of the silicon carbide powder and the aluminum powder, the mass of the surfactant is 0.5-25wt% of the mass of the organic binder, and the mass of the organic binder is 1-35wt% of the total mass of the FDM mixture; The FDM mixture is prepared into an aluminum silicon carbide composite material through an FDM printing step.

2. The FDM mixture according to claim 1, characterized in that: The particle size distribution of the silicon carbide powder is D50=0.5-150 μm.

3. The FDM mixture according to claim 1, characterized in that: The surfactant is selected from one or more of silane coupling agent, stearic acid, stearate, polyethyleneimine and tetramethylammonium hydroxide; And / or, the organic binder is one or more of a wax-based binder, epoxy resin, polyethylene glycol, high-density polyethylene, paraffin, polylactic acid, and ethylene-vinyl acetate copolymer.

4. The FDM mixture according to claim 1, characterized in that: The organic binder is a mixture of paraffin, ethylene-vinyl acetate copolymer and high-density polyethylene.

5. The method for preparing an FDM mixture suitable for FDM printing of aluminum silicon carbide composite materials according to claim 1, characterized in that: The preparation method comprises the following steps: mixing silicon carbide powder, aluminum powder and a surfactant to obtain a modified powder; kneading the modified powder with an organic binder, and then granulating to obtain an FDM mixture.

6. The preparation method according to claim 5, characterized in that The mixing is carried out by ball milling, the ball milling speed is 100 to 600 rpm, and the ball milling time is 0.5 to 10 hours; The mixing temperature is 130-180°C and the mixing time is 1-5 hours.

7. A method for preparing aluminum silicon carbide composite material based on FDM printing, characterized in that: The following steps are involved: The FDM mixture of claim 1 is used to perform FDM printing to form an aluminum silicon carbide composite material preform; the preform is thermally degreased to obtain a blank; the blank is infiltrated with aluminum by a pressureless infiltration method to obtain the aluminum silicon carbide composite material.

8. The method according to claim 7, characterized in that FDM printing is completed using an FDM type 3D printer with a nozzle temperature of 150-200°C, a printing platform temperature of 90-120°C, and a nozzle aperture of 0.4-1 mm.

9. The method according to claim 7, characterized in that: The pressureless infiltration process includes: using an inert atmosphere, an infiltration temperature of 700 to 1000° C., and an infiltration time of 0.5 to 5 hours.

10. The aluminum silicon carbide composite material prepared by the method according to claim 7, characterized in that: The density of the aluminum silicon carbide composite material is 2.60-3.00 g / cm 3 , three-point bending strength is 150-300MPa, thermal conductivity is 80-200W / m*K, thermal expansion coefficient is 5-15*10 -6 / K; the volume fraction of SiC in the aluminum silicon carbide composite material is in the range of 1 to 80%.